Isolation of a lytic bacteriophage against virulent Aeromonas hydrophila from an organized equine farm. (8th January 2016) - Anand, Taruna; Vaid, Rajesh Kumar; Bera, Bidhan Ch.; Singh, Jitender; Barua, Sanjay; Virmani, Nitin; K., Rajukumar; Yadav, Neeraj Kumar; Nagar, Dinesh; Singh, Raj K.; Tripathi, B.N.
Abstract : A bacteriophage (VTCCBPA6) against a pathogenic strain of Aeromonas hydrophila was isolated from the sewage of an organized equine breeding farm. On the basis of TEM analysis, phage belonged to family Myoviridae. PCR amplification and sequence analysis of gp 23 gene (encoding for major capsid protein) revealed phylogenetic resemblance to T4 like virus genus. Protein profiling by SDS‐PAGE also indicated its resemblance to T4 like phage group. However, the comparison of its gp 23 gene sequence with previously reported phages showed similarity with T4‐like phages infecting Enterobacteriaceae instead of Aeromonas spp. Thus, to our knowledge, this report points toward the fact that a novel/evolved phage might exist in equine environment against A. hydrophila, which can be potentially used as a biocontrol agent.